2000
DOI: 10.1017/s0021859699007947
|View full text |Cite
|
Sign up to set email alerts
|

A note on the effect of air temperature during gestation on birth weight and neonatal mortality of kids

Abstract: Analyses were made on birth weight of 2706 kids (six genetic groups) under confinement conditions in the arid zone of northern Mexico, to study the effect of air temperature (mean annual temperature l 21n1 mC) during gestation on this trait. The relationship of environmental temperature at kidding and survival of kids was also studied. Birth weight was significantly negatively related to mean dry bulb air temperature during gestation (reduction of 40p3 g for 1 mC increase in mean air temperature during gestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Kids are susceptible to low temperatures (Shelton and Groff 1984;Buddle et al 1988;Mellado et al 2000;Aldomy et al 2009), with kids of low birthweight being at a higher risk of hypothermia (Allan et al 1992b). At Condobolin, 62% of all perinatal kid losses in Australian rangeland and crossbred goats occurred when the chill index was above 950 kJ/m 2 .h (Bajhau and Kennedy 1990).…”
Section: Starvation Mismothering and Exposurementioning
confidence: 99%
“…Kids are susceptible to low temperatures (Shelton and Groff 1984;Buddle et al 1988;Mellado et al 2000;Aldomy et al 2009), with kids of low birthweight being at a higher risk of hypothermia (Allan et al 1992b). At Condobolin, 62% of all perinatal kid losses in Australian rangeland and crossbred goats occurred when the chill index was above 950 kJ/m 2 .h (Bajhau and Kennedy 1990).…”
Section: Starvation Mismothering and Exposurementioning
confidence: 99%
“…É consenso na literatura que fatores genéticos e ambientais, como as oscilações na disponibilidade e qualidade das pastagens, em consequência das condições climáticas, e no manejo nutricional e sanitário aplicado aos animais em cada ano, exercem influência sobre o peso ao nascer e sobrevivência dos cabritos (Silva & Araújo, 2000, Mellado et al, 2000Marai et al, 2002).…”
Section: Resultsunclassified
“…It seems likely that protein and/or fat tissue could have been catabolised in the foetus during heat stress periods. Mellado et al (2000) found that high air temperatures during late gestation had a limited influence on the birth weight of goat kids in Mexico. The effect of temperature on foetal growth restriction of kids in this experiment may be related to the cumulative effect of several months of high air temperatures, i.e.…”
Section: Discussionmentioning
confidence: 97%